International Bee Research Association (IBRA) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
International Bee Research Association (IBRA)The International Bee Research Association (IBRA) is the world information service for bees and beekeeping, Its headquarters are in Cardiff, UK and although it was set up in 1949 as the Bee Research...